The effects of N-Acetylcysteine on bile duct ligation-induced liver fibrosis in rats - EREN, FATİH (SPRINGER, 2007)
Stellate cells are activated by free radicals, and synthesize collagen. N-acetylcysteine (NAC) is a precursor of reduced glutathione and a potent scavenger of hydroxyl radicals and has potential antifibrotic effects. We aimed to test the effects of NAC on bile duct ligation (BDL) induced liver damage in rats. Forty-seven Wistar rats were divided into 5 groups: group 1, BDL + NAC (n = 10); group 2, BDL (n = 10); group 3, sham + NAC (n = 10); group 4, sham (n = 10); and group 5, control group (n = 10). NAC (50 mu mol/kg per day) or saline of single doses were administered intraperitoneally for 28 days. Serum biochemical and liver oxidative stress parameters were studied. Liver collagen level was determined by the method of Lopez de Leon and Rojkind. Liver slides were stained by hematoxylin and eosin and Masson trichrome\Gomory reticulum staining. Aspartate aminotransferase (AST) and alkaline phosphatase levels in the BDL + NAC group were lower than the BDL group and were higher than the control groups (all P < .001). Malondialdehyde, luminal, and glutathione levels in group 1 were lower than the BDL group (P = .01, P = .002, and P < .001) and higher than the control groups (all P < .001). NAC had no effect on alanine aminotransferase (ALT), gammaglutamyl transferase, bilirubin, albumin, or lucigenin levels. Liver collagen levels were higher in the BDL groups (P < .001); however, NAC had no effect on the collagen levels. The BDL groups showed stage 3 fibrosis; all the control groups were normal. NAC improved some biochemical parameters (AST, alkaline phosphatase) and oxidative stress parameters (malondialdehyde, luminol, glutathione) in the BDL model. NAC was found to be effective on cholestasis-induced hepatotoxicity. However, NAC was inefficient as an antifibrotic agent within a 1-month period of administration in the BDL model.
Keywords: antifibrotic; N-acetylcysteine; bile duct ligation; hepatic fibrosis; rat; HEPATIC STELLATE CELLS; COLLAGEN TYPE-I; OXIDATIVE STRESS; LIPID-PEROXIDATION; REACTIVE OXYGEN; GLUTATHIONE; BLEOMYCIN; MELATONIN; DAMAGE; ANTIOXIDANTS